Sodium hydrosulfide prevents hypertension and increases in vascular endothelial growth factor and soluble fms-like tyrosine kinase-1 in hypertensive pregnant rats - Possomato-Vieira, Jose Sergio [UNESP]; Gonçalves-Rizzi, Victor Hugo [UNESP]; Graça, Tamiris Uracs Sales [UNESP]; Nascimento, Regina Aparecida [UNESP]; Dias-Junior, Carlos A. [UNESP] (Springer Nature, 2016)
Sodium hydrosulfide (NaHS) has presented antihypertensive and antioxidant effects and may reduce circulating soluble fms-like tyrosine kinase-1 (sFlt-1). We examined whether NaHS prevents maternal and fetal detrimental changes in a model of hypertension in pregnancy induced by N(G)-nitro-L-arginine methyl ester (L-NAME). Forty pregnant rats were divided into four groups (n = 10 per group): Norm-Preg, Preg + NaHS, HTN-Preg, or HTN-Preg + NaHS. Systolic blood pressure (SBP), number of viable fetuses, litter size, pups, and placentae weights were recorded. Circulating plasma sFlt-1, vascular endothelial growth factor (VEGF), myeloperoxidase (MPO), trolox equivalent antioxidant capacity (TEAC) levels, and biochemical determinants of nitric oxide (NO) formation were assessed. SBP values were elevated in the HTN-Preg group on gestational days 16, 18, and 20. However, HTN-Preg + NaHS group presented lower SBP values on days 18 and 20. Lower number of viable fetuses and litter size were found only in HTN-Preg group compared to other. Reductions in placental weight were found in HTN-Preg and HTN-Preg + NaHS groups. Increases in fetal weight were found only in Preg + NaHS group. Increases in circulating sFlt-1 and VEGF levels were observed only in HTN-Preg group compared to other. Higher MPO and lower TEAC plasma levels were found in HTN-Preg + NaHS and HTN-Preg groups. NO was diminished in HTN-Preg animals, and NaHS treatment increased NO levels only in hypertensive pregnant animals. Treatment with NaHS prevents hypertension in pregnancy and concomitantly reduces circulating plasma sFlt-1 and VEGF levels; this correlates with improved litter size with more viable fetuses and increase in NO levels. However, these beneficial effects presented no relation with oxidative stress.
Keywords: Hydrogen sulfide donor; N(G)-nitro-L-arginine methyl ester; Preeclampsia; Rats